DESIGNING ROUTE DISTRIBUTION USING TWO PHASE TABU SEARCH ON HETEROGENOUS FLEET VEHICLE ROUTING PROBLEM WITH TIME WINDOW IN PT. XYZ TO MINIMIZE TRAVEL DISTANCE - Citra Septi Brilliane; Ari Yanuar Ridwan; Rio Aurachman (International Journal of Innovation in Enterprise System, 2019)
XYZ is a pasteurization milk processing company that produce milk drink from pure cow milk. PT. XYZ don’t sell their product directly to end user, instead they distribute their product to many companies which serve milk for their employees or operators in lunch time. So, their customer is mostly a manufacture company from various kinds of industry. They have about 40 customers and most of them are outside Bandung. However, the delivery may not be done as planned. The average on time delivery is around 96%. it is below PT. XYZ target which is 98%. The impact of the delay itself is vary between customers. Because when delay occur, each customer has their own regulation that has been settled in agreement contract. Based on the delay recapitulation above, there are several factors that caused this problem. Delay in departure is the most influential factors. It is because PT. XYZ don’t have fixed schedule of delivery and they miscalculate the departure time because of improper route determination that also leads to longer travel time. This case is categorized as Vehicle Routing Problem with Heterogeneous Fleet and Time Window (VRPHFTW) that will be solved using one of meta-heuristics algorithm which is Two Phase Tabu Search Algorithm to minimize travel distance. In the end, the travel distance can be minimized 19.48%. Keywords—Vehicle Routing Problem with Heterogenous Fleet and Time Window (VRPHFTW), Meta-Heuristics, Two Phase Tabu Search Algorithm.